Theoretical orientations and adaptations of the Montessori system for exceptional children in inclusive schools - Suarez, Ma. Rosario B. (2009)
The study was conducted to examine and analyze the Montessori system in relation to other learning theories and to establish its applicability for exceptional children in inclusive schools in the Philippines. The researcher employed the questionnaire, classroom observation and focus group discussion. The results identified specific groups of teachers which included those who adhered to the traditional Montessori system and those who were oriented to other learning theories. Results based on the classroom environment showed that the Montessori system is still being applied for exceptional chlldren. Adaptations were made to the Montessori materials in response to the Philippine setting. The Montessori system is being implemented in the classrooms where teachers use the prescribed materials and apply the principles in its presentation.